Overview and developmental analysis of China's technical and vocational education and training - Fan, Yinghui; Zheng, Haiyan; Ebonite, Romeo Salvo; Asis, Werson Role De; Juanatas, Ronaldo Antalan (International Journal of Innovative Research and Scientific Studies, 2024)
Vocational and technical education and training (TVET) in China is a key pathway to enhance labor productivity and drive economic development. Since the initiation of reforms and opening up, under the high attention of the Chinese government, we have experienced rapid development, from quantity expansion to quality improvement. This article delves into the current status and development trends of vocational and technical education in China, analyzing it from various aspects such as the legal environment, infrastructure, teacher enhancement, teaching methods, and cultural context. This paper conducts macro-research and analysis through policies and regulations and refers to relevant papers from Google Scholar and CNKI for micro-analysis. A telephonic interview was carried out with a total of 38 participants from four different vocational schools, industries, and enterprises. The user conducted similarity and differentiation comparisons using both Excel and Mind Mapping software. The research shows that China's vocational education market has entered a phase of rapid growth, and online education has also seen substantial development. However, due to China's vast territory and constraints arising from economic development and regional disparities, as well as diverse ethnic and cultural factors, vocational education and training (TVET) still faces numerous challenges, such as uneven economic and industry development, urban-rural disparities, teacher shortages, and the separation of schools and enterprises. This article aims to provide insights into the development of vocational and technical education and training from the perspectives of personalized education, talent cultivation, and talent needs. It is intended to expand and enhance the influence of vocational education development and broaden the perspective of vocational and technical talents.